The perspective of allied health staff on the role of nurses in subacute care. Issue 21 (23rd July 2018) - Digby, Robin; Bolster, Danielle; Perta, Andrew; Bucknall, Tracey K
Abstract : Aims and objectives: To explore allied health staff perceptions on the role of nurses in subacute care wards. Background: A consequence of earlier discharge from acute hospitals is higher acuity of patients in subacute care. The impact on nurses' roles and required skill mix remains unknown. In the same way, nurses' integration into the rehabilitation team is ambiguous. Design: Descriptive qualitative inquiry. Methods: Semistructured interviews conducted with 14 allied health staff from one subacute care facility in Melbourne, Australia. Interviews were audio‐recorded and transcribed verbatim. Analysis using the framework approach. Results: Three main themes were evident: (a) the changing context of care: patient acuity, rapid patient discharge and out‐dated buildings influenced care; (b) generalist as opposed to specialist rehabilitation nurses: a divide between traditional nursing roles of clinical and personal care and a specialist rehabilitation role; and (c) interdisciplinary relations and communication demonstrated lack of respect for nurses and integrating holistic care into everyday routines. Conclusions: Allied health staff had limited understanding of nurses' role in subacute care, and expectations varied. Power relationships appeared to hamper teamwork. Failure to include nurses in team discussions and decision‐making could hinder patient outcomes. Progressing patients to levels of independence involves both integrating rehabilitation into activities of daily living with nurses and therapy‐based sessions. Promotion of the incorporation of nursing input into patient rehabilitation is needed with both nurses and allied health staff. Relevance to clinical practice: Lack of understanding of the nurses' role contributes to lack of respect for the nursing contribution to rehabilitation. Nurses have a key role in rehabilitation sometimes impeded by poor teamwork with allied health staff. Processes in subacute care wards need examination to facilitate more effective team practices inclusive of nurses. Progressing patients' independence in rehabilitation units involves activities of daily living with nurses as much as therapy‐based sessions.